Case Report: Prolonged Anorexia With Nausea Caused by Immune Checkpoint Inhibitors for Malignant Melanoma Treated Using Kampo Medicines Bukuryoingohangekobokuto and Ninjin’yoeito - Takayama, Shin; Arita, Ryutaro; Ishii, Tadashi (Frontiers in Pharmacology, 2022)
Immune checkpoint inhibitors (ICIs) are indicated for several cancers, including malignant melanoma. Anorexia and nausea resulting in malnutrition are side effects of ICIs. In such cases, conventional drugs are used for symptom relief, but the symptoms may persist. We report a case of advanced malignant melanoma with prolonged anorexia and nausea, which occurred after nivolumab administration, and was successfully treated using Kampo medicines. A 75-year-old man with nasal bleeding visited our hospital. A nasal scope revealed an obstructive tumor in the left nasal concha. Tissue biopsy showed malignant melanoma, and computed tomography showed metastasis to the liver and bone. Thus, the patient was diagnosed with stage IV malignant melanoma. He received radiotherapy (30 Gy) and nivolumab with ipilimumab four times, followed by nivolumab administration alone. During the administration of nivolumab, he complained of severe anorexia and nausea, with a numeric rating scale (no symptoms, 0; severe symptoms, 10) score of 10. He could not consume food because of these symptoms, even after nivolumab administration was discontinued. His blood pressure was 92/59 mmHg, his performance status (PS; no fatigue, 0; bedridden or disabled, 4) was 4, and his body weight gradually decreased from 60 kg to 39 kg in a month. The patient showed malnutrition and dehydration and experienced anxiety and depression. Nivolumab was terminated, and conventional symptomatic drugs were prescribed, but the symptoms persisted. We then prescribed 9.0 g/day of ninjin’yoeito (TJ-108, Tsumura and Co.) to allow recovery from anorexia and subsequently added bukuryoingohangekobokuto (TJ-116, Tsumura and Co.) to treat the persistent nausea. After treatment with these two Kampo medicines, the patient’s appetite gradually recovered. Along with the recovery of nutritional status, his PS improved to 0, his anxiety and depressive state improved, and his body weight increased to 60 kg. The patient remained in good condition without cancer recurrence. The patient’s clinical course shows the usefulness of Kampo medicine as supportive care for symptom relief and maintenance of nutritional and mental status during cancer treatment.